1997
DOI: 10.1017/s1357729800016544
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dietary nitrogen and purine bases to the duodenal digesta: comparison of duodenal and polyester-bag measurements

Abstract: Four ewes fitted with ruminal and duodenal T-piece cannulas were given four diets in a 4 X 4 factorial design. Diets consisted of 700 (HF) or 400 (LF) g/day of ammonia-treated barley straw supplemented respectively with 150 or 600 g/day of concentrate made up with barley plus either soya-bean meal (SBM) or fish meal (FM) as the protein source, offered at 2-h intervals. Duodenal flows of digesta were estimated by the dual-phase technique using Co-EDTA and Yb-acetate as markers and ( 15 NH 4 ) 2 SO 4 was infused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…but consistent with the results reported by Perez et al (1997), there were large differences between the 15 N-enrichment of duodenal total N and duodenal purine N. This is an indication that duodenal purines are predominantly of microbial origin and reflects the relatively greater ruminal degradability of feed purines compared to the degradability of total feed N. Perez et al (1997) found a significant contribution (from 13 to 27% in whole digesta and from 2 to 17% in solid digesta) of feed purines to the duodenal purine flow in sheep and suggested that feed purines flow mainly with liquid duodenal digesta. Our data show feed purine contribution (based on 15 N-enrichment data) to duodenal liquid digesta purines of 3.5% (averaged between the two diets) and to duodenal solid digesta purines of 19.7%.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…but consistent with the results reported by Perez et al (1997), there were large differences between the 15 N-enrichment of duodenal total N and duodenal purine N. This is an indication that duodenal purines are predominantly of microbial origin and reflects the relatively greater ruminal degradability of feed purines compared to the degradability of total feed N. Perez et al (1997) found a significant contribution (from 13 to 27% in whole digesta and from 2 to 17% in solid digesta) of feed purines to the duodenal purine flow in sheep and suggested that feed purines flow mainly with liquid duodenal digesta. Our data show feed purine contribution (based on 15 N-enrichment data) to duodenal liquid digesta purines of 3.5% (averaged between the two diets) and to duodenal solid digesta purines of 19.7%.…”
Section: Discussionsupporting
confidence: 94%
“…The contribution to whole digesta purines was on average 9.1%. However, unlike results by Perez et al (1997), microbial purines comprised on average 96.5% of the liquid digesta purines. Work using real-time PCR has shown that DNA released as a result of plant cell lysis into duodenal contents is degraded almost instantaneously (Alexander et al 2004).…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations